The factors influencing the unemployment among fresh graduates in Kelantan / Noraini Ibrahim and Emylia Syafika Mohammed Fauzi - Ibrahim, Noraini; Mohammed Fauzi, Emylia Syafika (2022)
The title of this study is related to the factors that influence unemployment among fresh graduates in Kelantan. The objective used in this study is to find out whether the factors such as employability skills, English proficiency, Job mismatch, and demanding an unrealistic salary. The four objectives were selected to find out whether these factors influence unemployment among fresh graduates conducted in Kelantan. Furthermore, the method used in completing this study is through a questionnaire that was distributed using Google Forms to 394 respondents. Of these 394 respondents, a total of 202 men and 192 women had involved themselves in answering the questions posed by the researcher through questionnaires and references. In this study, researchers have identified the factors related to unemployment that occur among fresh graduates in Kelantan. The findings of the study show that unemployment among new graduates in Kelantan is due to many factors, especially lack of English proficiency and job mismatch. Therefore, new graduates should play an appropriate role in positioning themselves as employees to reduce unemployment.